Analysis and design of quadratic parameter varying (QPV) control systems with polytopic attractive region. Issue 8 (May 2018) - Rotondo, Damiano; Johansen, Tor Arne
Abstract: This paper proposes a gain-scheduling approach for systems with a quadratic structure. Both the stability analysis and the state-feedback controller design problems are considered for quadratic parameter varying (QPV) systems. The developed approach assesses/enforces the belonging of a polytopic region of the state space to the region of attraction of the origin, and relies on a linear matrix inequality (LMI) feasibility problem. The main characteristics of the proposed approach are illustrated by means of examples, which confirm the validity of the theoretical results.